Vernacular architecture en algeria “M’zab” = Arquitectura vernacula en argelia “M’zab” - Amine Rais, Mohamed El; Tendero Caballero, Ricardo (Building & Management, 2019)
AbstractThe present work focuses on the bioclimatic aspect in vernacular construction through a study of the traditional architecture of M’zab. The question posed is how this architecture could be useful and what techniques and strategies are adopted to result in such energy performance in a delicate area of its climate? Can we adopt the same principles to build a contemporary building as energetically efficient? It is a question of studying the solutions proposed in this architecture. To achieve this goal, we will look the characteristics of the M’Zab area, and what tools and approaches are being mobilized to ensure thermal comfort without the help of technology.ResumenEl presente trabajo se centra en el aspecto bioclimático en la construcción vernácula a través de un estudio de la arquitectura tradicional de M’zab. La pregunta planteada es cómo esta arquitectura podría ser útil y qué técnicas y estrategias están adaptadas para dar como resultado un rendimiento energético tan delicado en un área delicada de su clima. ¿podemos adoptar los mismos principios para construir un edificio contemporáneo como energéticamente eficiente? Se trata de estudiar las soluciones propuestas en esta arquitectura. Para lograr este objetivo, veremos las características del área de M’Zab, y qué herramientas y enfoques se están movilizando para asegurar el confort térmico sin la ayuda de la tecnología